Epidemiological, Clinical and Paraclinical Profile of Paediatric Malaria at University Hospital Centre Amissa Bongo in Franceville, Gabon - Roméo Karl Imboumy-Limoukou; Jean Claude Biteghe-Bi-Essone; Sandrine Lydie Oyegue-Liabagui; Jean Jordan Ekogha-Ovono; D’Alva Noronha Ingrid Nascimento; Steede Seinnat Ontoua; Cherone Nancy Mbani Mpega Ntigui; Lady Charlène Kouna; Jean Bernard Lekana-Douki (Nigerian Postgraduate Medical Journal)
Background: Malaria remains the deadliest parasitic disease and continues to cause more than half a million deaths across the world each year, mainly victims are sub-Saharan children. Malaria is a common reason for paediatric hospitalisation. Objective: The objective was to characterise malaria and describe the evolution after treatment in the paediatric department of the University Hospital Centre Amissa Bongo de Franceville. Methods: This was a cross-sectional study conducted from 1 February 2023 to 15 May 2023. A clinical and biological diagnosis was made in febrile children aged from 6 months to 15 years. Results: A total of 306 patients were included. The mean age was 50.4 ± 44.3 months, 94.3% had consulted within ≥48 h and self-medication was practiced by 83.3%. The prevalence of malaria was 17.3%. Fever ˃39°8C (adjusted odds ratios [aOR] = 2.68; 95% confidence interval [CI] = [1.32–5.48]; P < 0.01), chills (aOR = 2.14; 95% CI = [1.13–4.11]; P < 0.01) and nausea–vomiting (aOR = 2.03; 95% CI = [1.06–3.83]; P = 0.03) were the factors associated with the occurrence of malaria. The majority of children were treated for simple malaria with artemisinin-based combination therapy. A total of 16/53 was seen in post-therapeutic consultation. Of them, 2 patients had a positive thick drop. Conclusion: Non-compliance with preventive measures and the misuse of antimalarials further complicate the clinical picture, requiring parenteral management for the most part.